2016
DOI: 10.1177/0886260516645571
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Evaluation of Services Provided to Domestic Violence Survivors at Shelters in Bosnia-Herzegovina

Abstract: The shelter movement in Bosnia-Herzegovina was born out of a tradition of assisting survivors of gender-based violence in the early 1990s during the Bosnian conflict. To date, nine shelters are in existence providing emergency shelter and services to survivors. Little is known about these shelters, or the clients these shelters serve. The purpose of this study is to examine what services are provided to domestic violence survivors by shelters in Bosnia-Herzegovina and who these survivors are. A total of 43 ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Further, Dan & Banu, 2018 addressed the violence that Roma women experienced from other family members, such as their fathers. In addition, Muftić et al (2019) and Briones-Vozmediano et al (2019) studied the use of victim assistance services of Roma women victims of IPV, while Kozubik et al (2020) addressed the physical and mental health consequences for Roma women victims of IPV. These studies were conducted in Bosnia-Herzegovina, Slovakia, Spain, Romania and Turkey.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, Dan & Banu, 2018 addressed the violence that Roma women experienced from other family members, such as their fathers. In addition, Muftić et al (2019) and Briones-Vozmediano et al (2019) studied the use of victim assistance services of Roma women victims of IPV, while Kozubik et al (2020) addressed the physical and mental health consequences for Roma women victims of IPV. These studies were conducted in Bosnia-Herzegovina, Slovakia, Spain, Romania and Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the Roma were found to distrust victim assistance services and accordingly, did not use them. In Bosnia-Herzegovina, Muftić et al (2019) studied 433 services that provided help to domestic violence survivors. Their findings revealed that, on average, shelters had assisted 64 survivors in the previous year, typically married women with minor children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, the provision of shelter in safe houses was introduced as an additional measure of protection (Muftić, Deljkić, and Fansher 2019). 4 This measure is also rarely approved by the courts, in clear violation of official legislation.…”
Section: The Materials Basis Of Gender-based Violence: a Political Ecomentioning
confidence: 99%
“…Since 1993, following the opening of the first shelter in Zenica (within the Federation of BiH), a total of nine shelters (six in the Federation and three in Republika Srpska) with 204 beds have come into operation to assist females and children of DV (Logar, 2016). Included within the range of services available for survivors in BiH have been legal and medical advocacy, crisis intervention, individual counseling, support groups, and community education and awareness (Muftić, Deljkić, & Fansher, 2016). In addition to an increase of shelters and services for survivors since the 1990s, in 2013 the country ratified the Council of Europe Convention on Preventing and Combatting Violence Against Women and Domestic Violence (hereinafter the Istanbul Convention).…”
Section: Current Studymentioning
confidence: 99%